2023
DOI: 10.1007/s10680-023-09671-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and Universal Fertility Recuperation in Kazakhstan

Abstract: The fertility rates of Kazakhstan have reversed to levels not seen for several decades. The striking fertility increase poses questions regarding the extent to which this new development is shared across socio-demographic groups and the nature of fertility recuperation. The current study employs UNICEF Multiple Indicator Cluster Survey data and event-history modelling to analyse parity progressions to one, two, three, and four children. The results suggest a sustained fertility increase that is not merely asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In terms of the mechanisms of the association between religious affiliation and contraceptive use, it was found that part of the effect of religious belonging was mediated through short-term fertility intentions. Based on previous studies of Kazakhstan that reveal ethnic differentials in fertility and different stages of demographic transition for the two ethnic and religious groups in the country, and thereby different levels of demand for children (Kan 2023), one could assume that mediation through fertility intentions would explain much more of the variation in contraceptive use between Muslims and Christians. However, despite having the strongest effect of all potential mediators for both women and men, it still explains only a fraction of the variation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of the mechanisms of the association between religious affiliation and contraceptive use, it was found that part of the effect of religious belonging was mediated through short-term fertility intentions. Based on previous studies of Kazakhstan that reveal ethnic differentials in fertility and different stages of demographic transition for the two ethnic and religious groups in the country, and thereby different levels of demand for children (Kan 2023), one could assume that mediation through fertility intentions would explain much more of the variation in contraceptive use between Muslims and Christians. However, despite having the strongest effect of all potential mediators for both women and men, it still explains only a fraction of the variation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies in Kazakhstan have focused on religion as the primary independent variable concerning reproductive behaviour, whereas several studies have examined ethnic differentials. Several studies have thus assessed ethnic differentials between Kazakhs and Russians in fertility intentions and preferences as well as parity progressions (Agadjanian 1999;Agadjanian, Dommaraju, and Glick 2008;Agadjanian, Dommaraju, and Nedoluzhko 2013;Spoorenberg 2013Spoorenberg , 2015Kan 2023). Kan (2023) finds a sustained fertility increase across all birth orders during the 2000s that is shared across both main ethnicities in the country.…”
Section: Reproductive Behaviourmentioning
confidence: 99%
See 2 more Smart Citations